ROLE OF LEGAL COMPLIANCE IN TRANSFORMATION OF MICROFINANCE INSTITUTIONS INTO MICROFINANCE BANKS IN KENYA - Koome Rukaria, Dr. George (IJRDO - Journal of Business Management, 2017)
The purpose of this study was to establish the role of legal compliance in the transformation of microfinance institutions into microfinance banks in Kenya. The target population was 48 members of the Association of Microfinance Institutions as at 1st January 2013. Using purposive sampling, the study selected 25 institutions from which 100 respondents were selected using simple random sampling. A questionnaire was used to collect data. This study established that legal compliance had a significant effect on the transformation of microfinance institutions into microfinance banks in Kenya. Thus, it concluded that legal compliance played a significant role in the transformation of microfinance institutions into microfinance banks in Kenya. The study recommends that for transforming Microfinance Institutions to comply with the legal requirements with ease, they should first fully understand the licensing process. The study also recommends further research to determine the impact of regulating microfinance in Kenya.